Role of lncRNAs in cis‐ and trans‐regulatory responses to salt in Populus trichocarpa. (14th March 2022) - Ye, Xiaoxue; Wang, Shuo; Zhao, Xijuan; Gao, Ni; Wang, Yao; Yang, Yanmei; Wu, Ernest; Jiang, Cheng; Cheng, Yuxiang; Wu, Wenwu; Liu, Shenkui
SUMMARY: Long non‐coding RNAs (lncRNAs) are emerging as versatile regulators in diverse biological processes. However, little is known about their cis ‐ and trans ‐regulatory contributions in gene expression under salt stress. Using 27 RNA‐seq data sets from Populus trichocarpa leaves, stems and roots, we identified 2988 high‐confidence lncRNAs, including 1183 salt‐induced differentially expressed lncRNAs. Among them, 301 lncRNAs have potential for positively affecting their neighboring genes, predominantly in a cis‐ regulatory manner rather than by co‐transcription. Additionally, a co‐expression network identified six striking salt‐associated modules with a total of 5639 genes, including 426 lncRNAs, and in these lncRNA sequences, the DNA/RNA binding motifs are enriched. This suggests that lncRNAs might contribute to distant gene expression of the salt‐associated modules in a trans ‐regulatory manner. Moreover, we found 30 lncRNAs that have potential to simultaneously cis‐ and trans ‐regulate salt‐responsive homologous genes, and Ptlinc‐NAC72, significantly induced under long‐term salt stress, was selected for validating its regulation of the expression and functional roles of the homologs PtNAC72.A and PtNAC72.B ( PtNAC72.A/B ). The transient transformation of Ptlinc‐NAC72 and a dual‐luciferase assay of Ptlinc‐NAC72 and PtNAC72.A/B promoters confirmed that Ptlinc‐NAC72 can directly upregulate PtNAC72.A/B expression, and a presence/absence assay was further conducted to show that the regulation is probably mediated by Ptlinc‐NAC72 recognizing the tandem elements (GAAAAA) in the PtNAC72.A/B 5′ untranslated region (5′‐UTR). Finally, the overexpression of Ptlinc‐NAC72 produces a hypersensitive phenotype under salt stress. Altogether, our results shed light on the cis ‐ and trans ‐regulation of gene expression by lncRNAs in Populus and provides an example of long‐term salt‐induced Ptlinc‐NAC72 that could be used to mitigate growth costs by conferring plant resilience to salt stress. Significance Statement: Evidence of the cis ‐ and trans ‐regulation of gene expression by lncRNAs under salt stress is lacking. Here, we demonstrate the limits of cis ‐regulation versus the limitless trans ‐regulation of lncRNAs in potentially regulating gene expression under salt stress, and also demonstrate that Ptlinc‐NAC72 functions in delayed negative feedback under long‐term salt stress that could be exploited to maximize salt tolerance, thereby mitigating growth costs.